Register Of Sociolinguistic Used In Forum Vape Purchasing On Facebook - Gustav Gloor, Hanzl; Dzaky Kamaluddin, Ahnaf (LPPM Universitas Duta Bangsa Surakarta, 2023)
This study aims to analyze the language register used on online vape buying and selling forums in Indonesia. The data was obtained from forum members’ postings and conversations over three months. The method used was observe with the note-taking technique. The analytical framework used register theory and sociolinguistics. The results showed that vape buying and selling forums have a unique register characteristic, which includes (1) the use of special vape terms and acronyms, such as vape, RDA, RBA; (2) many elements of youth slang, such as lu, gua, bro; (3) casual and tending to informal language style; and (4) the main topics discussed were buying and selling vape products and devices. Sociolinguistic factors such as age, gender, social and educational backgrounds influence the language variations that emerge. Registers on vape buying and selling forums are dynamic and influenced by the development of the vape community itself. The implication is that understanding the register of online forums helps effective communication between members.